Homo Moralis and regular altruists II - Aslihan Akdeniz; Christopher Graser; Matthijs van Veelen (Tinbergen Institute, 2023)
Alger and Weibull (2013) ask the question whether a combination of assortative matching and incomplete information leads to the evolution of moral or altruistic preferences. Their central result states that Homo Hamiltonenis – a type that has moral preferences with a morality parameter equal to the level of assortment – is evolutionarily stable, while preferences that lead to different behaviour are unstable. Together with their claim that altruistic and moral preferences differ sharply, this suggests that moral preferences tend to beat altruistic ones in evolutionary competition. We show that this is not true. First of all, we show that there is a loophole in the definition of evolutionary stability, allowing for Homo Hamiltonensis to satisfy the definition when the set of equilibria is empty, and their equilibrium behaviour is not determined. If we try to close this loophole, by allowing for mixing, or by allowing for asymmetric equilibria, we find that there are two options. With the first approach, the differences in behaviour between Homo Hamiltonensis and regular altruists can be substantial, but as soon as the difference appears, Homo Hamiltonensis can be invaded, and regular altruists win in direct competition. With the second way of allowing for mixing, or coordination on asymmetric equilibria, Homo Hamiltonensis cannot be invaded, but then the difference in behaviour all but disappears, as all equilibria between Homo Hamiltonensis are also equilibria between regular altruists. Classification-JEL:
Keywords: 330; Altruism; morality; evolution; assortment; incomplete information.